2016
DOI: 10.1007/s00264-016-3118-2
|View full text |Cite
|
Sign up to set email alerts
|

Successful osteoconduction but limited cartilage tissue quality following osteochondral repair by a cell-free multilayered nano-composite scaffold at the knee

Abstract: Osteochondral repair by implanting the MaioRegen® scaffold provides a successful osteoconduction and filling of the cartilage defect. However there is evidence for a limited repair cartilage tissue quality at 18 months after the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 25 publications
4
36
1
Order By: Relevance
“…Perdisa et al [23] showed satisfactory clinical results at 60 months of follow-up, regardless of the defect size, suggesting the appropriateness of this procedure to treat also large OCD lesions. Nevertheless, MRI findings reported an incomplete bone regeneration, as reported also in other studies [24], demonstrating the difficulty to properly regenerate a physiologic subchondral bone tissue. To this regard, better results were proved for another procedure able of restoring the entire osteochondral unit in a single surgical procedure [22], the transplantation of fresh osteochondral allografts [25].…”
Section: Discussionsupporting
confidence: 79%
“…Perdisa et al [23] showed satisfactory clinical results at 60 months of follow-up, regardless of the defect size, suggesting the appropriateness of this procedure to treat also large OCD lesions. Nevertheless, MRI findings reported an incomplete bone regeneration, as reported also in other studies [24], demonstrating the difficulty to properly regenerate a physiologic subchondral bone tissue. To this regard, better results were proved for another procedure able of restoring the entire osteochondral unit in a single surgical procedure [22], the transplantation of fresh osteochondral allografts [25].…”
Section: Discussionsupporting
confidence: 79%
“…In this study, 2 patients were re-operated due to treatment failure and were excluded from the results. None of the patients showed a complete regeneration of the subchondral bone [119][120][121]…”
Section: Chondromimetic (Tigenix Belgium)mentioning
confidence: 97%
“…Since this report the clinical trials have been discontinued in Denmark and it is advised that MaioRegen be used with caution.Yan et al have examined the outcomes of clinical trials on 8 patients, and reported that subchondral edema, schlerosis and cyst were observed in most of the cases. A complete integration of the scaffold into the border zone was described; however, T2 mapping data and the zonal T2 index significantly differed in the repair tissue compared to the healthy control cartilage (P < 0.001) which indicates a limited quality of the repair cartilage obtained using this scaffold119 as observed inFigure 9.…”
mentioning
confidence: 95%
“…5 a Volumetric bone mineral density (vBMD) of OA samples according to both cartilage grading and depth; b presence of a large cyst (white arrows) in an osteoarthritis sample (pQCT image) [ 84 ] and microCT image
Fig. 6 a CT scan failed to show bone ingrowth ( arrow ) into TruFit plug [ 90 ]; b T2 mapping MRI scan of OC lesion repair after 18 months by the use of the MaioRegen scaffold, and bone cysts are observed [ 96 ]. With permissions from Elsevier and Springer
Fig.
…”
Section: Lessons From Clinical Osteochondral Scaffolds and What We Hamentioning
confidence: 99%
“… a CT scan failed to show bone ingrowth ( arrow ) into TruFit plug [ 90 ]; b T2 mapping MRI scan of OC lesion repair after 18 months by the use of the MaioRegen scaffold, and bone cysts are observed [ 96 ]. With permissions from Elsevier and Springer …”
Section: Lessons From Clinical Osteochondral Scaffolds and What We Hamentioning
confidence: 99%